Model Pengembangan Sistem Informasi Pendaftaran Online Pasien Pada Klinik Gigi Dentika Berbasis User Centred Design - Jully Triansyah; Rusma Insan Nurachim; Susi Ermawati; Sandra Dewi Saraswati; Vivi Maria (Jurnal Sistem Komputer dan Informatika (JSON), 2021)
In today's online-based era, the use of websites in carrying out patient registration procedures is very useful. Dental Clinic Dentika is one of the dental clinics located in the Tangerang area and has quite a number of patients. In the procedure for registering patients for examination, they still use a manual system, where patients come directly and wait in line for the examination. This is deemed ineffective because long lines can occur at a certain time. This web-based online patient registration is to make it easier for patients to register themselves when they are going to take medication or dental care without having to come to the clinic first. Another advantage is that it makes it easier for clinical administrative staff to serve patient registration, increases time efficiency in terms of patient care and facilitates patient data management. The User Centered Design (UCD) method is one of the right methods to solve the problem of patient registration at the Dentika Dental Clinic. This method looks at the needs of the user or users in designing an information system. The result of this study is a website that can be accessed by patients to register for the examination